Damnatio Memoriae Cesarza Gety w inskrypcjach z Brytanii - Daria Janiszewska-Sieńko (In Gremium. Studies in History, Culture and Politics, 2025)
Presented historical study has been based mainly on epigraphic sources from Roman Britain from the period 202-212 AD. It focuses on the damnatio memoriae of the younger son of the emperor Septimius Severus, Geta, whose name was erased from monuments erected in Roman forts in Britain. The author attempts to reconstruct the image of inscriptions and the manner in which the destruction was carried out and also peruses for reestablishing the memory of damned Caesar.